(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article investigates the role of authentic texts in enhancing reading and writing skills in foreign language education. Authentic texts, such as newspaper articles, literary excerpts, and real-life documents, provide learners with exposure to natural language usage, cultural context, and varied linguistic structures. The study aims to analyze how integrating authentic materials into classroom instruction can improve learners’ comprehension, vocabulary acquisition, and writing proficiency. Using a qualitative research design, classroom observations, learner feedback, and analysis of writing tasks were employed to evaluate the effectiveness of authentic texts in promoting language skills.